St. Lucia National Language Policy - Ministry of Education, Sustainable Development, Innovation, Science, Technology and Vocational Training (Ministry of Education, Sustainable Development, Innovation, Science, Technology and Vocational Training, 2018)
This policy document establishes an effective framework for the consideration and use of the native languages of the peoples of St. Lucia. It serves to protect and promote the use of local languages and the development of language skills needed to meet national education standards. The National Language Policy appreciates the multi-linguistic nature of our society and supports the participation of all citizens in the life in our nation, regardless of language.
Keywords: language policy; national language